Long-term effects of medication for opioid use disorder in children. Issue 4 (April 2022) - Cox, Jamie; Reid, Nancy; Lander, Laura
ABSTRACT: Opioid maintenance therapy in pregnant patients can result in children born with neonatal abstinence syndrome (NAS). These infants are at high risk for poor school performance, unemployment, and criminal activity because they never reach the neurocognitive levels of their peers. This article discusses the neurocognitive development consequences of medicated opioid use disorder on infants and children and methods to help them reach their potential into adulthood.